Artisanal ceramic factories using wood combustion: A nanoparticles and human health study - Martinello, Kátia (2021)
The ceramics industry, resulting from developments of modern compounds, is a segment of great influence in worldwide sustainability. Artisanal ceramic factories based on wood combustion have significant risks for the creation and discharge of atmosphere nanoparticles (NPs) and ultra-fine particles (UFPs). At present, there is insufficient recognition on the influence of engineered-NPs on the atmosphere and health. Real improvements are indispensable to diminish contact with NPs. The present study demonstrates the main NPs and UFPS present in an area of intense artisanal wood-combustion ceramic manufacturing. Particulate matter was sampled for morphological, chemical, and geochemical studies by sophisticated electron microbeam microscopy, X-Ray Diffraction, and Raman spectroscopy. From NPs configuration (<10 nm) we identify nucleation. Several amorphous NPs (>10 nm) were produced around the studied artisanal ceramic factories. This study presents an indication of the recent information on population and work-related contact to NPs in the artisanal ceramic factories and their influence on health.